Enhancing Disaster Preparedness: Development of an Android Mobile Application for Real-time Disaster Reporting, Notification, and Danger Zone Visualization - Han, Jun (Auckland University of Technology, 2024)
In the face of increasing disasters, effective disaster preparedness and response are crucial. Nowadays, smartphones are widely used by everyone. In the case of a disaster, it’s possible to use mobile technology to allow general public to report incidents and alert them about the events and the location of emerging disaster danger zones. Currently, disaster and emergency mobile applications can be categorized into two types: Early warning systems and Location-based alert systems. Early warning systems provide alerts to mobile users if a disaster occurs, however, these applications often lack detailed information about the disaster events and direct users to visit a website for more information. On the other hand, location-based alert systems allow users to receive alerts and information by setting up their location in the application. However, if users fail to set a location, they will not receive any alert about the disaster. All current mobile applications only passively receive alerts and cannot enable users to directly report disaster events. This research focuses on enhancing disaster preparedness through the development of an Android mobile application prototype designed for real-time disaster reporting, notification, and danger zone visualization. The application prototype allows users to report disasters as they occur, receive timely notifications about ongoing threats, and visualize affected areas on a mobile phone map. This helps the public to avoid entering into hazardous areas and allows emergency services to efficiently dispatch equipment and materials. Furthermore, this application prototype is evaluated through disaster simulations among the general public. The feedback is discussed in terms of both potential benefits and limitations. Suggestions for future development work are also provided.